Pengaruh Merger dan Akuisisi Terhadap Return Saham, Abnormal Return dan Trading Volume Activity pada Perusahaan Jasa Sub Sektor Telekomunikasi yang Terdaftar Di Bursa Efek Indonesia - Arieska Mellynia, Mega; Agung Nugroho, Ari; Zukhri, Nizwan (CV. Lafadz Jaya, 2023)
Mergers and acquisitions are corporate actions carried out by companies which can affect the price of securities, such as shares, or bonds issued by that company. This study aims to analyze differences in stock returns, stock abnormal returns, and trading volume activity before and after mergers and acquisitions. The sample of this study amounted to 3 companies after applying purposive sampling technique. The approach in this research is through event study analysis with an observation period of five days before and five days after the merger and acquisition event. Data management in this study was carried out using the paired sample t test which aims to determine whether there is a difference in average between two groups of samples that are interconnected with the help of SPSS 26.The results of this study found that there was a market reaction as evidenced by the significant difference between stock returns, stock abnormal returns, and trading volume activity before and after the merger and acquisition event. The results of the paired sample t test show the stock return value with sig (0.000) <0.05, abnormal stock return with sig (0.001) <0.05 and trading volume activity with sig value. (0.008) <0.05.